An innovative strategy to investigate microbial protein modifications in a reliable fast and sensitive way: A therapy oriented proof of concept based on UV-C irradiation of SARS-CoV-2 spike protein - Sergio Strizzi; Letizia Bernardo; Pasqualina D'Ursi; Chiara Urbinati; Andrea Bianco; Fiona Limanaqi; Andrea Manconi; Maria Milanesi; Alberto Macchi; Dario Di Silvestre; Adalberto Cavalleri; Giovanni Pareschi; et al. (Elsevier, 2023)
The characterization of modifications of microbial proteins is of primary importance to dissect pathogen lifecycle mechanisms and could be useful in identifying therapeutic targets. Attempts to solve this issue yielded only partial and non-exhaustive results. We developed a multidisciplinary approach by coupling in vitro infection assay, mass spectrometry (MS), protein 3D modelling, and surface plasma resonance (SPR). As a proof of concept, the effect of low UV-C (273 nm) irradiation on SARS-CoV-2 spike (S) protein was investigated. Following UV-C exposure, MS analysis identified, among other modifications, the disruption of a disulphide bond within the conserved S2 subunit of S protein. Computational analyses revealed that this bond breakage associates with an allosteric effect resulting in the generation of a closed conformation with a reduced ability to bind the ACE2 receptor. The UV-C-induced reduced affinity of S protein for ACE2 was further confirmed by SPR analyses and in vitro infection assays. This comprehensive approach pinpoints the S2 domain of S protein as a potential therapeutic target to prevent SARS-CoV-2 infection. Notably, this workflow could be used to screen a wide variety of microbial protein domains, resulting in a precise molecular fingerprint and providing new insights to adequately address future epidemics.